ANALISIS SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU (STUDI KASUS SEKOLAH DASAR NEGERI 1 BLIMBING KECAMATAN BOJA) - Purdiyanti; Noor Miyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Academic supervision is a task that must be carried out by a school principal, but the reality is that academic supervision is not carried out optimally, this happens even in the majority of schools in Boja District. Supervision carried out so far is only a formality, ignoring the main function, namely providing supervision to teachers so that teachers can evaluate teaching methods in class whether they are less than optimal with facts in the field when related to the different characters of all students, so that the vision and mission for creating professional teachers has not yet been achieved. Therefore, academic supervision must really be carried out by the principal for a minimum of one meter at a time with the aim of improving teacher performance, both in terms of time and academic discipline, so that professional teachers can be created so that students will be more optimal in participating in the learning process.The implication of this research is the principal's academic supervision of teacher performance to improve the quality of students' education in the Blimbing 1 State Elementary School (SD), Boja District. If the principal's academic supervision is carried out well and regularly in accordance with predetermined regulations, it is certain that teacher performance will also increase so that it can have an impact on the quality of good education.